A novel approach to assessing the prevalence and drivers of illegal bushmeat hunting in the serengeti - Nuno, Ana (Conservation biology : the journal of the Society for Conservation Biology, 2013)
© 2013 The Authors. Conservation Biology published by Wiley Periodicals, Inc., on behalf of the Society for Conservation Biology.